Educational robotics summer camp at IPB - Gonçalves, José (2020)
Robotics in education has special relevance in current digital society where students should know how to deal with technology. In this paper, it is presented an educational experiment in the mobile robotics domain. The referred experiment was part of a summer camp, which took place at the Polytechnic Institute of Bragança Portugal, being its technological aspects related with mobile robotics. Other than the technological aspects, the students participated in many different cultural and social activities, having the opportunity to know the city of Bragança and also to know different persons, mainly students, professors, researchers and laboratory technicians. The applied approach in the summer camp was a challenge based learning methodology, being involved in the experiment 3 professors, 4 monitors, working with a group of 16 secondary school students. The described experiment was planned as an activity of the RoboSTEAM - Integrating STEAM and Computational Thinking development by using robotics and physical devices ERASMUS+ Project.